Technology-Aided Assessment of Sensorimotor Function in Early Infancy - Allievi, Alessandro G.; Arichi, Tomoki; Gordon, Anne L.; Burdet, Etienne (Frontiers in Neurology, 2014)
There is a pressing need for new techniques capable of providing accurate information about sensori-motor function during the first 2 years of childhood. Here we review current clinical methods and challenges for assessing motor function in early infancy, and discuss the potential benefits of applying technology-assisted methods. We also describe how the use of these tools with neuroimaging, and in particular functional magnetic resonance imaging (fMRI), can shed new light on the intra-cerebral processes underlying neurodevelopmental impairment. This knowledge is of particular relevance in the early infant brain which has an increased capacity for compensatory neural plasticity. Such tools could bring a wealth of knowledge about the underlying pathophysiological processes of diseases such as cerebral palsy; act as biomarkers to monitor the effects of possible therapeutic interventions; and provide clinicians with much needed early diagnostic information.